PEMODELAN GEOSTATISTIK UNTUK MENGETAHUI SEBARAN KANDUNGAN GAS METHANE DAN POROSITAS PADA SEAM BATUBARA FORMASI WARUKIN DIDAERAH TAMIANG LAYANG KAB. BARITO TIMUR - PUTRA, IMAM MUHAJJIR FAKHRI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This study was conducted to determine coal seam which has high permeability as coalbed methane reservoir. Determination of high permeability zones was approached by using grid model of high anomaly value of porosity log and high anomaly value of gas content, both lateral and vertical distribution. Good coal permeability zones have a high reflection of log porosity values and gas content values. Porosity log values used in this study was calculated using the method of Serra (Serra. 1984) based on short density log ( SD ) and long density log ( LD ) data input, while the gas content values using the equation of Kim (Kim , 1977). To determine porosity log value and gas content value on particular wells which have no data, a regression linear equation has been employed. After porosity log value and gas content value on the whole point of all well already recovered, then further step for estimating value of porosity log and gas content, both lateral and vertical distribution on all grid areas can be modeled by using linear regression for cokriging method. Coal seam zone on North East (NE) deposit has a very high kernel density anomaly index, however it has a very low anomaly value of porosity logs and gas content. It is interpreted that those may be effected by intensively tectonic activity on this side areas. As a result, causing changes in direction of cleats orientation. In addition, uplifting has changes coal seam deposit closed to the surface and make weathering index become much higher, consequently coal might to be powdered. The coal powder may fill openings pulverization of cleats and impede flow of gases and fluids. Coal seam deposit in research area that has a high distribution value of log porosity is located on the Southwest (SW). This is caused by cleat permeability in this zone is formed with excellent under traction (burial) conditions which occurred by the result of uplifting on North East (NE) of research area. Result of lineament extraction shown in this potential zone is not much influenced by excessive tectonic intensity, so that the lineament is not much developed. Trend of overall anomalies of gas content on each coal seam shows a high anomaly with increasing depth of overburden which influence the accumulation of hydrostatic pressure. By increasing hydrostatic pressure, gas content value in coal seam will be higher. Total gas in place resources inside sweet polygon area (650,8 Ha) having a high anomaly value of porosity log and gas content is 540.55 MM SCF approximately. Anomaly of gas content values inside sweet polygon area were obtained by using Kim equation (Kim, 1977), has showed different trends with anomaly of porosity log values. The difference between trend of porosity logs values and gas content values (Kim, 1977), can be answered through gas desorption isotherm formula which has proposed by the authors in this study. The difference of those trend is due to the interconnection with the cleat fracture system outer equilibrium pressure (disequilibrium pressure). Consequently, accumulation of gas at high porosity coal seam zones migrate toward lower hydrostatic pressure zones